Instrumentation and methods for rapid estimation of selected viscoelastic parameters in foods. Issue 4 (20th July 2021) - Sakurai, Naoki; Takashima, Tatsuki; Akimoto, Hidemi; Blahovec, Jiří
Abstract: A new method to estimate the selected viscoelastic parameters of foods using damped vibration analysis is presented for the evaluation of fruits and baked products. A flat disk is attached to the flat sample surface using a laser rangefinder that measures the sample thickness in advance, and it is locked by a trigger. Next, the trigger is released to allow the probe to press the sample through the force of gravity. The damped vibration of the probe caused by the deformation of the food is measured by monitoring the displacement of the probe via a linear encoder. The bulk modulus and viscosity are estimated using the fractional Zener model and mass. Young's modulus ( E ) is estimated independently by determining the maximum velocity of the probe using Hooke's law. Poisson's ratio ( ν ), and the shear modulus and viscosity are calculated by employing the estimated E and bulk modulus. The bulk modulus, bulk viscosity, shear modulus, shear viscosity, and E of apples were found to be higher than those of bananas. The bulk modulus, bulk viscosity, E, and shear modulus for white bread were lower than those for pound cake, but the ν values were higher, whereas those of sponge cake were intermediate. After drying the baked products for 1 day, most of the parameters of the samples increased, but the value of ν for white bread decreased. The proposed free‐falling device estimated the four viscoelastic coefficients, Poisson's ratio, and Young's modulus of the food sample in less than 1 s. Abstract : A new method to estimate the six viscoelastic parameters using a damped vibration analysis is developed for food evaluation. A flat disk probe pushes the food sample by gravity force with a free‐falling device. The free‐falling device estimated the bulk modulus, bulk viscosity, shear modulus, shear viscosity, Young's modulus, and Poisson's ratio of the food in less than 1 s.